Longitudinal Reading Performance Comparison and its Variation with Print, Mobile and Social Media Tools - Xiangming, Li; Li, Xuening; Song, Menghong; Zhang, Jingshun (International Journal of Emerging Technologies in Learning (iJET), 2021)
A plethora of previous literature generated the mixture of results by comparing the reading outcome between digital and printed contexts. Further, the cross-sectional study above failed to yield the findings about the multi-session per-formance over a prolonged period of time as the reading activities proceeded. To address the gap, this study further explored the reading performance over a period of 12 weeks by designing the four-session frames for three different reading contexts of print, mobile and social media. Reading performance scores were gathered from186 postgraduate students from a research university in P.R. China. One-way ANOVA was conducted to compare the reading outcome among three reading contexts within each temporal session. The integrated statistical results showed that reading in social media produced the highest performance and reading in mobile the lowest performance across all the four temporal ses-sions. Longitudinal study revealed the consistency of reading performance in social media and in mobile with respectively high and low caliber over the four the reading sessions. Reading in print generated the performance in be-tween except in the second temporal session. Future efforts could direct to the comparison of text length between short and long with different textual genres.